The Faithful Rise Up: Split Identification and an Unlikely Change Effort - Gutierrez, Betzaluz; Howard-Grenville, Jennifer; Scully, Maureen A. (Academy of Management Journal, 2010)
Through a qualitative study of the emergence of unlikely activism from committed members of the Catholic Church, we examine how identification can trigger and shape a change effort. We uncover how crafting “split identification” allows members to retain their identification with normative aspects of an institution, while disidentifying with, and seeking to change, organizational aspects. Our process model traces how members split their identification, attempt to repair the split by seeking change, and respond when their claimed identification is challenged. We offer implications for identification theory and for literature on change originating inside organizations and institutions.